Kajian Stilistika Novel Student Hidjo Karya Mas Marco Kartodikromo - Maulidia Tifani Alfin Nur Hardiana (Journal of Social, Culture, and Language, 2023)
Language and literature have a close relationship in their studies. Stylistic study is a form of study that uses an objective approach. Because in terms of the objectives of the study and the resulting explanations, stylistic studies are studies that focus on the form of the use of sign systems in literary works which are obtained rationally-empirically and can be accounted for. This stylistic study in Student Hidjo's novel seeks to describe the selection of language sound aspects (assonance and alliteration), to describe the use of diction or word choices found in the novel, and to describe the style of language used in the novel Keywords: Stylistic studies, novels, literary genres